Studi Etnobotani Komparatif Tumbuhan Rempah yang Bernilai Sebagai Obat di Desa Tombi Kecamatan Ampibabo Kabupaten Parigi Moutong Sulawesi Tengah - Hari Rusdwi Novitasiah; Eny Yuniati; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2012)
Research on etnhobotany comparative study of spice plants that used by some tribes in Tombi village, Ampibabo district, Parigi Moutong regency, Central Sulawesi. This research is conducted from November to Desember 2012. The aims of this research is gathering information about the spices of plants and herbs thats used, the type of disease that can solved by the herbs and the way to use the herbs. The type of research was descriptive research through the semi structured interviews with 25 respondents using media question form. The analysis of the data used in this research is the IBM SPSS version 20. The results of the study showed that there were 29 plants species used spice as medicine. The part of plants is used as follows leaves, fruit, the stem, seeds, rhizomes, a corm, the root and sap. The societies of Tombi village use some of herbs of spices as a medicine to treat a chronic, uncontagious disease and for health care. The manner of its use is boiled, pounded, chewed, squeezed, grase, burned, and sliced before served. Based on dendogram, we can conclude that most of the people in Tombi village speacially Kaili Lauje tribes use the species of spice plants as a medicine. Key words: Ethnobotany, spice plants,Tombi village